Local control and fracture risk following stereotactic body radiation therapy for non-spine bone metastases. Issue 2 (May 2018) - Erler, Darby; Brotherston, Drew; Sahgal, Arjun; Cheung, Patrick; Loblaw, Andrew; Chu, William; Soliman, Hany; Chung, Hans; Kiss, Alex; Chow, Edward; Poon, Ian
Abstract: Aims: To report local control and toxicity rates for patients treated with stereotactic body radiotherapy (SBRT) for non-spine bone metastases. Methods and materials: Eighty-one patients with 106 non-spine bone metastases were treated between 2011 and 2014 and retrospectively reviewed. Indications included: oligometastases (63%), oligoprogression (17.3%), retreatment (2.4%) or other (17.3%). Cumulative incidence function was used to assess local recurrence and fracture probability. Bivariate relationships were investigated based on selected patient, tumour and dose–volume factors. Results: Mean follow-up was 13 months (range, 0.25–45.6) and the median patient age was 66.4 years (range, 36–86). Most patients were male (60.5%) and the predominant histology prostate cancer (32%). Bone metastases were most commonly located in the pelvis (41.5%) and almost half sclerotic. The most common prescriptions were 30 Gy/5 (30.2%) and 35 Gy/5 (42.5%). The cumulative incidence of local recurrence at 6, 18 and 24 months respectively was 4.7%, 8.3% and 13.3% with a mean time to local recurrence of 11.8 months (range, 3.9–23.4). A significant association was found between local recurrence and volume of the PTV ( p  = 0.02), with larger PTVs having a greater risk of local failure. Fracture was observed radiographically in the treatment volume in 9/106 (8.5%) of treated lesions and the mean time to fracture was 8.4 months (range, 0.7–32.5 months). With respect to predictors, a trend was observed for lytic lesions ( p  = 0.11) and female gender ( p  = 0.09). Conclusions: The results of this study confirm that SBRT yields high rates of long-term local control for non-spine bone metastases with a low fracture risk.